(untitled) (Educational Knowledge, 2016)
Currently, technology is integrated into all aspects of society, and it is the younger generations who are most familiar with its technical use; these young people are now called "digital natives." This quantitative research aimed to characterize the use of technological resources available to them, both at school and at home, by fifth and sixth grade students at the Escuela España in the city of Osorno, Chile. This study serves to enhance teachers’ understanding of their students, enabling them to guide their actions based on the students’ skills and abilities. Among the findings, it is noteworthy that, despite the fact that the students studied come from families classified as "vulnerable," they have access to various technologies such as televisions, telephones, and laptops with internet access at home. These resources are primarily used for entertainment activities, given their extensive use of Web 2.0 platforms, such as the social network Facebook and the video portal YouTube. It was also discovered that the educational institution has a wide variety of technological resources, which are used by both teachers and students. These resources are primarily traditional: computers, printers, and multimedia projectors, but lack cameras and interactive whiteboards.